2019
DOI: 10.29252/j.health.10.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Review of Co-Composting Municipal Sewage Sludge with a Variety of Biological Waste

Abstract: Background & objective: Direct application of sewage sludge in agriculture has been limited due to the presence of pathogens, inappropriate fermentation of organic waste and the presence of heavy metals. Co-composting of sewage sludge with biological waste is a method to reuse waste that leads safe disposal of sludge and waste. The purpose of this study was to review the advantages of co-compost and the possibility of compost production from a mixture of sewage sludge and biological waste. Method: In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The pH values in the early stages of the process were 7.7 and 7.5 for TW2 and TW3 piles, respectively. Degradation of OM and accumulation of organic acids can decline pH at the beginning of the process (Zazouli and Ala 2019). Generally, the values of pH for both piles after the 2 nd week gradually increased to a rate of 8.5 in the 5 th week.…”
Section: Composting Process and Abiotic Factorsmentioning
confidence: 97%
See 2 more Smart Citations
“…The pH values in the early stages of the process were 7.7 and 7.5 for TW2 and TW3 piles, respectively. Degradation of OM and accumulation of organic acids can decline pH at the beginning of the process (Zazouli and Ala 2019). Generally, the values of pH for both piles after the 2 nd week gradually increased to a rate of 8.5 in the 5 th week.…”
Section: Composting Process and Abiotic Factorsmentioning
confidence: 97%
“…As indicated in Table 1, in the early stages, the number of fecal streptococci increased to 7 logs MPN/g DW and 7.9 logs MPN/g DW in TW2 and TW3, respectively and after that, these bacteria decreased in both piles. (Zazouli 2019) and (Nafez et al 2013) reported that the total coliforms have lower values in returned piles in the stability phase. Also in (Ma et al 2019) study, the number of fecal coliforms and Streptococci in compost piles decreased from log 5 and log 2.49 to log 2.27 and log 2.12, respectively.…”
Section: Indicator and Pathogenic Microorganismsmentioning
confidence: 97%
See 1 more Smart Citation